(untitled) (Journal of the College of Education for Women, 2019)
Find addresses some issues of contemporary stylistic contemporaryArab scholars, and tries to answer. Issue: stylistic roots in the rhetoricalArab heritage. And the issue of reverse between old and contemporary.And proposes a new stylistic take into account the specificity of the Islamicand Arabic text is consistent with the application and analysis.